Controlled self-organization of cyanostilbene: emission tuning and photo-responsiveness. Issue 28 (29th June 2016) - Yang, Minmin; Xing, Pengyao; Ma, Mingfang; Zhang, Yimeng; Wang, Yajie; Hao, Aiyou
Abstract : Well-defined self-assembly structures based on a photo-controlled cyanostilbene derivative (CMD) were successfully constructed in mixed solvent systems of H2 O/THF. Under UV light irradiation, the nanostructures could be changed with enhanced emission. Abstract : Cyanostilbene modified with dimethylaniline (CMD) could self-assemble into vesicles and fibrous morphologies depending on the solvophobic properties. Furthermore, morphology of well-defined nanostructures could be changed with enhanced emission triggered by the photo-isomerization of cyanostilbene. The present system has potential for building luminescent color conversion materials.